Primary Care Physician’s Knowledge of Bee Venom Allergy, Treatment and Adrenaline Auto Injector Usage Skills (Annals of Medical Research, 2021)
None
Keywords: Anaphylaxis; İnsect Sting Allergy; Auto İnjector.